2016
DOI: 10.3758/s13423-015-0993-2
|View full text |Cite
|
Sign up to set email alerts
|

Mind wandering minimizes mind numbing: Reducing semantic-satiation effects through absorptive lapses of attention

Abstract: Mind wandering is associated with perceptual decoupling: the disengagement of attention from perception. This decoupling is deleterious to performance in many situations; however, we sought to determine whether it might occur in the service of performance in certain circumstances. In two studies, we examined the role of mind wandering in a test of Bsemantic satiation,^a phenomenon in which the repeated presentation of a word reduces semantic priming for a subsequently presented semantic associate. We posited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…This is, however, somewhat ironic because many researchers have largely been interested in examining unintentional mind-wandering [3335,8289], and to this end, they have often presented participants with tedious and boring tasks to elicit unintentional mind-wandering (e.g., sustained-attention and vigilance tasks; [14,67,9095]). However, given that (1) people’s level of motivation tends to be rather low when they experience boredom [96,97], and (2) decreases in motivation levels are associated with increases in intentional mind-wandering [41], it might be that the common employment of boring tasks in the context of research on mind-wandering has inadvertently elicited intentional mind-wandering.…”
Section: Mind-wandering Can Occur With or Without Intentionmentioning
confidence: 99%
“…This is, however, somewhat ironic because many researchers have largely been interested in examining unintentional mind-wandering [3335,8289], and to this end, they have often presented participants with tedious and boring tasks to elicit unintentional mind-wandering (e.g., sustained-attention and vigilance tasks; [14,67,9095]). However, given that (1) people’s level of motivation tends to be rather low when they experience boredom [96,97], and (2) decreases in motivation levels are associated with increases in intentional mind-wandering [41], it might be that the common employment of boring tasks in the context of research on mind-wandering has inadvertently elicited intentional mind-wandering.…”
Section: Mind-wandering Can Occur With or Without Intentionmentioning
confidence: 99%
“…Solving problems through spontaneous insight was associated with higher blink rates as compared to analytical problem solving (Salvi, Bricolo, Franconeri, Kounios, & Beeman, 2015). The relationship between mind wandering and blink rate is currently not clear (Mooneyham & Schooler, 2016; Smilek, Carriere, & Cheyne, 2010; Uzzaman & Joordens, 2011), but demanding internally focused cognition tasks like idea generation and insight problem solving are typically accompanied by higher blink rates (Akbari Chermahini & Hommel, 2012; Salvi et al, 2015; Ueda, Tominaga, Kajimura, & Nomura, 2015), supporting the hypothesis of an active decoupling strategy.…”
Section: Introductionmentioning
confidence: 99%
“…Answers to the multiplechoice questions were often repeated during the audiobook or could be derived from the storyline. This repetition can lead to mind wandering and loss of attention, yet studies have shown that this would only affect performance in case strong detachment from the task occurs (Mooneyham and Schooler, 2016). Through observation, we were able to ensure participants were never fully losing attention to the speech stimulus.…”
Section: Discussionmentioning
confidence: 99%